2018
DOI: 10.1002/jgt.22390
|View full text |Cite
|
Sign up to set email alerts
|

A note on the maximum number of triangles in a C5‐free graph

Abstract: We prove that the maximum number of triangles in a C 5‐free graph on n vertices is at most 122(1+o(1))n3∕2, improving an estimate of Alon and Shikhelman.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 5 publications
(7 reference statements)
0
22
0
Order By: Relevance
“…The systematic study of the function ex(n, H, F ) was initiated by Alon and Shikhelman in [2], where they improved the result of Bollobás and Győri by showing that ex(n, C 3 , C 5 ) ≤ (1 + o(1)) √ 3 2 n 3/2 . This bound was further improved in [12] and then very recently in [13] by Ergemlidze and Methuku who showed that ex(n, C 3 , C 5 ) < (1 + o(1))0.232n 3/2 . Another notable result is the exact computation of ex(n, C 5 , C 3 ) by Hatami, Hladký, Král, Norine, and Razborov [28] and independently by Grzesik [21], where they showed that it is equal to ( n 5 ) 5 .…”
Section: Generalized Turán Problemsmentioning
confidence: 90%
“…The systematic study of the function ex(n, H, F ) was initiated by Alon and Shikhelman in [2], where they improved the result of Bollobás and Győri by showing that ex(n, C 3 , C 5 ) ≤ (1 + o(1)) √ 3 2 n 3/2 . This bound was further improved in [12] and then very recently in [13] by Ergemlidze and Methuku who showed that ex(n, C 3 , C 5 ) < (1 + o(1))0.232n 3/2 . Another notable result is the exact computation of ex(n, C 5 , C 3 ) by Hatami, Hladký, Král, Norine, and Razborov [28] and independently by Grzesik [21], where they showed that it is equal to ( n 5 ) 5 .…”
Section: Generalized Turán Problemsmentioning
confidence: 90%
“…Erdős [8] first determined ex(n, K t , K r ) for all t < r. Bollobás and Győri [3] determined the order of magnitude of ex(n, C 3 , C 5 ). Their estimate was improved by Alon and Shikhelman [1] and recently by Ergemlidze, Győri, Methuku and Salia [10]. Alon and Shikhelman obtained a number of results on ex(n, T, H) for different T and H and posed several open problems in [1].…”
Section: Short Proofs Of Two Theorems Of Luomentioning
confidence: 97%
“…The constant in the upper bound was improved to √ 3 3 by Alon and Shikhelman [1] and by Ergemlidze, Győri, Methuku and Salia [10]. Győri and Li [23] give bounds on ex(n, K 3 , C 2k+1 ).…”
Section: Introductionmentioning
confidence: 99%